Santos Basin continental shelf morphology, sedimentology, and slope sediment distribution - Alberto G. Figueiredo Jr.; Juliane Castro Carneiro; João Regis dos Santos Filho (Ocean and Coastal Research)
The ocean bottom morphology, depth, sediment grain size, sediment sorting, carbonate content, and water depth are used to compose seafloor maps as support for biological studies. Sediments are reworked by waves and currents and accumulate according to the hydrodynamic level on the continental shelf. In contrast, sediments are accumulated by pelagic settling, mass wasting, turbidity flows, and boundary currents on the slope. Sea level oscillations during the Quaternary also played an important role in modifying the shelf seabed's morphology and sedimentary mosaic composition. The work addresses these topics in the Santos Basin based on extensive bathymetric data, shallow seismic records, and stratified bottom sediment samples in water depths ranging from 25 to 2,400m, as part of The Santos Basin Regional Environmental Characterization Project (PCR-BS). The main objective is to provide broad background information on the sedimentology and morphology of Santos Basin, focusing on the continental shelf. The morphology, sediment supply, shelf orientation, and ocean climate imprint the Santos Basin's characteristics. The Northern shelf sector is the most dynamic because of the narrow shelf, steep gradient, and East-West shoreline orientation, providing conditions for storm waves to approach and mobilize sediment in the ocean bottom shallow than 50 m water depth. The Southern sector of the shelf is much broader than the Northern sector; it displays a gentler gradient, and its orientation is Northeast-Southwest; therefore, less subject to storm waves than the Northern sector.